PROBLEMATIK PERKULIAHAN PENERJEMAHAN DI JURUSAN PENDIDIKAN BAHASA INGGRIS - Widyahening, Ch Evy Tri (UNIVERSITAS SLAMET RIYADI, 2012)
Abstract The objective of this research is to discuss the problems on instruction of translation as one of the subject matter at the English Department IKIP PGRI Madiun. The specific objectives of the analysis are: the types of translation done at the English Department; the quality of translations by the students at the English Department; the types of error found in the studentsâ€™ translations at the English Department; and the comments of the students as well as the lecturers toward the instructions of translation in the English Department. The research was done during the fifth semester English Department covering three classes with 90 students in all. The research technique used were passive participating observation, in depth interviewing, taken from the office documents and the departmentâ€™s and facultyâ€™s archives. There were 20 students as informants who were selected by using â€œpurposive random samplingâ€, â€œcriterion based samplingâ€, â€œinternal samplingâ€, and â€œtime samplingâ€. The collected data were validated by prolonged involvement in the process, keener observation, and informant review. The main research analysis used is interactive analysis model according to Miles and Huberman (1984). The results of the research show that the teaching learning process was satisfactory; meaning in line with the objectives. Teaching media are sufficiently provided. Almost all types of translation have been covered in the instructions. But it is a problem for the lecturers because the studentsâ€™ errors are still abundant. Therefore, the qualities of their translations are still low. Â Keywords : The problem on instruction of translation, translation, case study